First case report of robot‐assisted radical cystectomy for bladder cancer that developed after salvage radiotherapy following radical prostatectomy for prostate cancer - Suguru Oka; Kazushige Sakaguchi; Michikata Hayashida; Shinji Ito; Kazuhiro Kurosawa; Shinji Urakami (IJU Case Reports, 2023)
Introduction Robot‐assisted radical cystectomy for bladder cancer that develops after curative treatment for prostate cancer has not yet been reported. Case presentation A 65‐year‐old man underwent radical prostatectomy and received salvage radiotherapy after his postoperative prostate‐specific antigen level failed to decrease. Nine years after radiotherapy, local recurrence and lung/bone metastases were observed, and he was started on androgen deprivation therapy. In the following year, he was diagnosed with nonmuscle invasive bladder cancer. He underwent transurethral resection of the bladder tumor once but had multiple recurrences within 3 months. As hematuria could not be controlled by transurethral surgery, he underwent robot‐assisted radical cystectomy without rectal injury. Since then, there has been no recurrence of either bladder or prostate cancer. Conclusion This is the first report of a successful robot‐assisted radical cystectomy for bladder cancer that developed after local salvage radiotherapy following radical prostatectomy for prostate cancer.